Pedagogical methodologies in Science to facilitate the teaching and learning of children with autism - Cipriano, Jéssyca Ananias; Duarte-Silva, Erica (Seven Editora, 2024)
The present work aims to seek methodologies and interventions through the autoethnographic work of the present researcher, university student and mother of a 5-year-old non-verbal autistic child, to help students, with this condition, in overcoming obstacles, developing socialization, of speech, with Science teaching as its generating theme. The method used was ethnography of school practice, an ethnological method for non-anthropologists with educational objectives. It is based on a review of scientific and educational literature, interviews and fieldwork. The following teaching practices were developed below. Use of applications: (1) Tiny puzzle (memory game; alphabet soup with complete alphabet; association of animal sounds with their shape); (2) Syllabando (forming syllables; learning the shape of letters; forming simple words with syllables). The following educational games were also developed: (1) Dynamics with alphabetic magnet; (2) ‘The beach’ dynamic; (3) Fruit and vegetable dynamics; (4) Book “Textures of Nature”; (5) Discovering the cycle of life; (6) Using ready-made toys. Finally, the researcher carried out participant observation at the municipal event: ’Autism in our lives’. Aimed at fathers, mothers and guardians of children with autism spectrum disorder (ASD). As a result, it was noticed that after stimulating his skills with the dynamics described, the research participant with ASD then began to have a new skill, hyperfocus starting to ask him to identify the words for him and speak the letters that form these words. This behavior occurs in various places such as food packaging, street signs, at school or at home. Finally, the work established a form of non-verbal communication between the child and the researcher-mother, enabling communication for the autistic child, learning about the world around him and literacy. As for the mother-researcher, this research enabled access to scientific and social events aimed at families with members with ASD, carrying out a voluntary scientific initiation, preparing a course completion work, and completing the undergraduate course, promoting with mastery, new horizons for this very capable family, which needs so little access, from means of communication (verbal, non-verbal) to fundamental rights to education for children and women. DOI:https://doi.org/10.56238/sevened2024.009-017